PENGARUH EKUITAS MEREK (BRAND EQUITY) TERHADAP PROSES KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA NMAX PADA DEALER YAMAHA TUGU MAS BIMA - Zultilhansyah Zultilhansyah; Intisari Haryanti (Universitas Sarjanawiyata Tamansiswa, 2020)
The lack of field salespeople has not achieved the desired target of thecompany. Increasing the level of competition between brands that makesthe main challenges that lead to decreased sales. The purpose of thisresearch is to study the valuation of Brand Equity on PurchasingDecisions. The sample in this study amounted to 96 people. Dataanalysis using a simple linear regression test and to test its significanceusing the T test. The results of this study indicate that the brand researchon Yamah NMAX motorcycle purchasing decisions at the Tugu MasDealer City of Bima. the magnitude of the effect of 65.3% is on strongrelationships, meaning that larger consumers who buy NMAXmotorcycles, decide to buy because this NMAX brand provides value andsatisfaction dedicated to consumers.Kata Kunci: Brand Equity, Purchasing Decisions